Developmental Delay and Oculo-Visual Deficits: Challenges and Interventions–A Narrative Review. - Kaiti, Raju; Shyangbo, Ranjila; Regmi, Aayusha; Kafle, Rachana (Optometry & Visual Performance, 2026)
Visual skills play a critical role in early childhood development, influencing not only visual acuity but also other domains, such as language, fine motor control, and social interactions. Disruptions in visual development can result in oculo-visual deficits, which are common in children with developmental delays. These deficits include issues with visual perception, oculomotor control, binocular vision, and visuo-cognitive processing. Developmental delay is characterized by significant delays in two or more developmental areas, and when combined with oculo-visual deficits, comprehensive care is essential. The prevalence of developmental disabilities among children under 20 is estimated to be between 10.1% and 11.3%, with oculo-visual deficits affecting 68% to 86% of this population. Risk factors include prenatal, perinatal, and postnatal influences. Children with developmental delays often experience difficulties in motor coordination, balance, laterality, and visual performance. Early recognition and intervention are vital in addressing these deficits, as they significantly impact overall development and quality of life. A multidisciplinary approach involving eye care professionals, occupational therapists, and caregivers is essential for effective rehabilitation. Vision therapy can improve visual perceptual skills and overall quality of life by addressing oculomotor dysfunction, binocular vision, and accommodation issues. Prioritizing early detection and intervention can optimize developmental outcomes for children with oculo-visual deficits and developmental delays. This review explores the prevalence of these deficits and highlights the crucial role of eye care professionals in their identification, management, and rehabilitation, aiming to enhance the longterm well-being of affected children.